Crusades - Jones, Terry, 1942-; Ereira, Alan. (New York, NY : Facts on File, 1995)
Nine hundred years ago Christian Europe was seized by a fever that changed the world. Inspired by a Pope who offered rewards on earth and a certain place in paradise thereafter, tens of thousands of men, women and children - knights and peasants, rich and poor, old and young - set out for the Holy Land to recapture the Holy City, Jerusalem, and save their fellow Christians from persecution by the Infidel. Crusades, and the television series which this book accompanies, tell the dramatic story of these events, and the reality behind the myths. This story of battles and betrayals, drama and intrigue, is told with wit and clarity, and is magnificently illustrated throughout in color. The authors show how the Europeans used the morality of the Crusades to justify the conquest and destruction of any society which stood in their way, sowing the seeds of fear, suspicion and even hatred in the Arab world - a legacy which remains to this day.
The world of a crusader -- The great adventure -- War in Anatolia -- The March to Jerusalem -- The Arab response -- The fight back begins -- St Bernard's dogs -- Arab unity -- Saladin the upstart -- The fall of Jerusalem -- To the rescue -- The battle of the heroes: Richard v. Saladin -- The fourth crusade -- A new kind of crusade -- Mongols and Mameluks.
Includes bibliographical references (pages 248-250) and index.
Keywords: Crusades